Corporate engagement with the community: building relationships through CSR - Abdullah, Azwan; Yaacob, Mohd Rafi; Ismail, Mohammad; Zakaria, Mohd Nazri; Abdullah, Zulhamri; Mohd Radyi, Siti Amaliya (Medwell Journals, 2017)
The rapid expansion of companies, particularly through their large scale projects has met with growing concerns within the local community over the social, environmental and economic impacts of such expansion. Failure by the companies to recognize and respond to these concerns may have an adverse effect on the long term commercial viability of their projects. Many giant companies today operate in highly regulated environments, demanding them to behave ethically and to be transparent. Companies are expected to resolve many social, environmental and economic issues such as poverty, climate change and many more. Corporate Social Responsibility (CSR) is a strategic initiative by the company to address these issues. Community engagement is one of the integral components of CSR. This serves as a platform for communication between the companies and the local community and also as viable means for their business sustainability. This study describes the importance of such engagement and the methods employed by companies in sustaining and building strong relationships with the local community and contributing towards their economic growth.